Barriers to participation of Aboriginal people in cancer care: communication in the hospital setting - Shahid, Shaouli; Finn, Lizzie; Thompson, Sandra (Australian Medical Association, 2009)
Background: Markedly poorer outcomes from cancer for Indigenous Australians need to be systematically explored. This paper reports Aboriginal views of one factor impacting upon willingness to access cancer care, that of effective communication between Aboriginal people and health service providers in Western Australian (WA) hospital settings. Design, setting and participants: Qualitative research involving 30 in-depth interviews with Aboriginal people affected by cancer from across WA. Outcome measures: Aboriginal views about the quality of communication within the hospitals, factors impairing communication and suggestions for improvement.Results: Factors crucial to effective patient-provider communication such as language, shared understanding, knowledge and use of medical terminology require attention. Additionally, communication between Aboriginal people and health professionals needs to be understood within a broader socio-cultural and political context. Fear of the medical system and being disempowered; mistrust; collective memories of the experience of colonisation and its aftermath; lack of understanding of Aboriginal customs, values, lifestyle, and the importance of family and land; and experiences of racism were key issues impairing communication. Non-verbal communication and the symbolism of hospital environments also posed problems. Conclusion: Several key areas emerged for the attention of health service providers in communicating and caring for Aboriginal people in the hospital setting. These include the importance of learning about the historical context of Aboriginal people and their access to health care, understanding Aboriginal values and lifestyle, and changing styles of communication, including symbolic and non-verbal modes. Measures to improve communication and facilitate Aboriginal access and participation in treatment are proposed.